A single-center, single-arm, prospective, open-label, and comparative trial to evaluate the safety and tolerability profile of a 90-day oral L-arginine hydrochloride intervention for patients with amyotrophic lateral sclerosis - Hiroyuki Naito; Masahiro Nakamori; Megumi Toko; Yuki Hayashi; Taku Tazuma; Tomoaki Watanabe; Keito Ishihara; Keisuke Tachiyama; Yu Yamazaki; Hirofumi Maruyama (Scientific Reports)
Abstract Weight loss, a key indicator of malnutrition in amyotrophic lateral sclerosis (ALS) patients, negatively impacts patient prognosis. However, effective nutritional interventions have not been adequately established. Research in ALS model mice has shown that L-arginine can prolong survival; however, no human intervention studies have been conducted. We conducted a single-center, single-arm, prospective, open-label, and comparative trial to assess the safety and tolerability of L-arginine hydrochloride in ALS patients. ALS patients were administered 15 g/day L-arginine hydrochloride for 90 days. The primary outcome of safety was evaluated on days 45 and 90. The secondary outcome of efficacy was evaluated by measuring nutritional status, ALS Functional Rating Scale (ALSFRS) scores, and the occurrence of events such as the initiation of tracheostomy positive pressure ventilation (TPPV) and death. The study included 20 patients (40% female; mean age, 62.0 ± 6.9 years; median disease duration, 1.9 years). Six participants (30%) experienced treatment-emergent adverse events (TEAEs), including elevated creatine kinase levels, liver function test abnormalities, glucose tolerance issues, hyperammonemia, anorexia, dysgeusia, and vasculitis. No serious TEAEs were associated with L-arginine hydrochloride. Over the course of three months, the average changes in body weight, body mass index, and the ALSFRS score were − 0.37 kg, -1.1 kg/m2, and − 1.7 points, respectively. There were no events requiring TPPV initiation or deaths. This study demonstrated that the oral administration of L-arginine hydrochloride over three months was well tolerated by ALS patients, with no serious TEAEs or deaths attributed to the study drug. Trial Registration number: Japan Registry of Clinical Trials (jRCTs061230001), first registered 11/04/2023.